RISK ANALYSIS AND IMPLEMENTATION OF RISK MANAGEMENT IN MUDHARABAH FINANCING: A LITERATURE REVIEW - Munawir, Al; Darmawan, Reza (Universitas Syiah Kuala, 2024)
This study aims to analyze the risk and risk management of mudharabah financing in Islamic banking. Islamic banking as an institution providing mudharabah financing will certainly face risks in the financing. The risk that is often found in mudharabah financing is non-performing financing. This risk will create other risks, namely financial, investment, compliance, legal, and fiduciary risks. The method used in this research is a literature study. The results show that the risk management of non-performing financing is rescheduling, reconditioning, and restructuring. Financial risk management can be overcome by applying the 5C principle. Investment risk can be overcome by monitoring and supervising mudharib. Compliance risk can be overcome through the screening process and educating mudharib regarding mudharabah contracts. Legal risk can be overcome by making Bank Syariah more thorough in verifying and validating documents submitted by mudharib and improving internal quality. Fiduciary risk can be overcome by forming a special division to screen competent mudharib candidates and check information from mudharib.